PLASTIC RECYLING IN INDONESIA BY CONVERTING PLASTIC WASTES (PET, HDPE, LDPE, and PP) INTO PLASTIC PELLETS - Hin Chandara Chandara; Sunjoto -; Sarto - (Master in Systems Engineering, 2015)
Due to the population growth, economic development, increasing the consumption of products patterns in Indonesia and activities of citizen, MSW has generated by 384 Indonesia cities was about 80,235 ton per day (or 320,940m3 per day). The plastics solid waste (PSW) become to the major concern after organic waste and significantly impact to in environment. In order to solve the problem this research is conducted to identify the potential raw material from plastics, in order to replaces the pure material of plastics pellets that is made from crude oil and minimize the effect bring to environment. This compendium is presented the concept of the appropriation technology for plastics recycling, it emphasize the typical method by converting plastics waste of thermoplastic type Polyethylene terephthalate (PET), High density polyethylene (HDPE), Low density polyethylene (LDPE) and Polypropylene (PP) into plastics pellets. Whereas thermoplastics chemical structure possible for recyclable , the mechanical recycling method is played as the best technology and common used in recycling of conventional plastic waste material into new raw material without changing basic structure. The quality of pellets that reprocess from the plastics waste is based on the effective factors of sorting, washing, drying and temperature of melting in each zones of extruder machine